Application of 3D Printing Technology in Minimally Invasive Pelvic Surgery - Sergey V. Donchenko; Karen A. Egiazaryan; Andrey A. Prokhorov; Aleksey V. Shabunin; Alexander D. Rubtsov; Alexander M. Nemnonov (Travmatologiâ i Ortopediâ Rossii)
Background. Due to the technological progress in traumatology, there are more opportunities to apply MIPO (minimally invasive plate osteosynthesis) techniques for treating pelvic ring injuries. However, such problems as implant malposition due to complicated intraoperative visualization and the risks of postoperative complications remain relevant.